Answer: Ok, we have two numbers, and one of them is an odd integer, and the other is even.
Lets call M to the odd integer and N the even.
We know that a even integer can be written as 2k, where k is a random integer, and a odd integer can be written as 2j + 1, where j is also a random integer.
then M = 2k, N= 2j+1
then the product of M and N is: M*N = 2*k*(2*j + 1) = 2*(k*2*j + k)
is obvious to see that (k*2*J + k) is a integer, because k and j are integers.
then if we call g = ( k*2*J + k), we can write M*N=2g, and we already know that this is an even number. So M*N is a even integer.